PENGARUH KEJELASAN SASARAN ANGGARAN, TRANSPARANSI DAN PENGENDALIAN AKUNTANSI DAN PENGENDALIAN AKUNTANSI TERHADAP KINERJA MANAJERIAL PADA PEMERINTAH PROVINSI SULAWESI UTARA - Natalia, Posumah Linda; Kalangi, Lintje; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2019)
The purpose of this study was to determine the effect of the clarity of budget targets, transparency and accounting control on managerial performance in the North Sulawesi provincial government both partially and simultaneously. This hypothesis was tested using the t test and F test. The population in this study were all employees who worked on SKPD on the research object, sample in this research are managers, namely employees who occupy from the echelon two to the echelon for, with amount of responder counted 50 people. The analytical method used in this research is multiple regression analysis. The result of the analysis through the t test stated that the clarity of the budget target effects on the managerial performance of the provincial government of North Sulawesi . The transparency does not affectÂ on the managerial performance of the province of North Sulawesi. The accounting control effects on the managerial performance of the province of North Sulawesi. The result of the analysis of the F test state that the clarity of budget targets, transparency and accounting control affect simultaneously on the managerial performance of the North Sulawesi province.